Uniform circuits and exclusive read PRAMs - Niepel, Inga; Rossmanith, Peter (1990)
Abstract: "CRCW-PRAMs can be characterized in terms of unbounded fan-in circuits with AND- and OR-gates. We introduce the notion of SELECT- gates. Combining this with the concept of an unambiguous circuit we are able to give a circuit equivalent of EREW-PRAMs, thus answering an open question of [SV84]. Moreover, circuits with SELECT-gates characterize CRCW-, CREW-, ERCW-, and EREW-PRAMs in a uniform manner."
Keywords: Parallel processing (Electronic computers); Random access memory